2023
DOI: 10.3390/ma16072892
|View full text |Cite
|
Sign up to set email alerts
|

Cometal Addition Effect on Superconducting Properties and Granular Behaviours of Polycrystalline FeSe0.5Te0.5

Abstract: The enhanced performance of superconducting FeSe0.5Te0.5 materials with added micro-sized Pb and Sn particles is presented. A series of Pb- and Sn-added FeSe0.5Te0.5 (FeSe0.5Te0.5 + xPb + ySn; x = y = 0–0.1) bulks are fabricated by the solid-state reaction method and characterized through various measurements. A very small amount of Sn and Pb additions (x = y ≤ 0.02) enhance the transition temperature (Tconset) of pure FeSe0.5Te0.5 by ~1 K, sharpening the superconducting transition and improving the metallic n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 63 publications
0
0
0
Order By: Relevance
“…The selected composition FeSe0.5Te0.5 is prepared at 600 °C for 21 h in the first step, and in the second stage, the sample is grounded and heated again at 600 °C for 4 h, as more detail was discussed in our previous studies [12,23]. This FeSe0.5Te0.5 sample shows the transition temperature up to 15 K by the convenient synthesis method at ambient pressure, as reported by the previous report [23] and depicted in Figure 8a. The temperature dependence of the resistivity (ρ) for (a) FeSe0.5Te0.5 prepared by in-situ and ex-situ processes using HP-HTS, where the samples were sealed in a Ta-tube before being placed inside the high-pressure chamber.…”
Section: Current Results Using This Hp-hts Facilitymentioning
confidence: 78%
See 2 more Smart Citations
“…The selected composition FeSe0.5Te0.5 is prepared at 600 °C for 21 h in the first step, and in the second stage, the sample is grounded and heated again at 600 °C for 4 h, as more detail was discussed in our previous studies [12,23]. This FeSe0.5Te0.5 sample shows the transition temperature up to 15 K by the convenient synthesis method at ambient pressure, as reported by the previous report [23] and depicted in Figure 8a. The temperature dependence of the resistivity (ρ) for (a) FeSe0.5Te0.5 prepared by in-situ and ex-situ processes using HP-HTS, where the samples were sealed in a Ta-tube before being placed inside the high-pressure chamber.…”
Section: Current Results Using This Hp-hts Facilitymentioning
confidence: 78%
“…Before using the high-pressure technique for these complicated families, the HP-HTS technique was applied to the simplest FBS, i.e., the 11 (FeSe) family. Tellurium (Te) doping at Se-sites, i.e., Fe(Se,Te), provides the highest transition temperature T c of 15 K for FeSe 0.5 Te 0.5 [23]. First, we synthesized the high-quality Fe(Se,Te) sample by the solid-state reaction method at ambient pressure (0 GPa).…”
Section: Current Results Using This Hp-hts Facilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Iron-based superconductors (FBS) were discovered in 2008 [1], and since then, numerous compounds have been identified belonging to this family [2,3]. These high T c materials can be categorized into six families based on the structure of the parent compounds, such as REFeAsO (RE1111; RE = rare earth), AFe 2 As 2 (122; A = Ba, K, Ca), (Li/Na)FeAs (111), thick perovskite-type oxide blocking layers, such as Sr 4 V 2 O 6 Fe 2 As 2 (22,456), Sr 4 Sc 2 O 6 Fe 2 P 2 (42,622), etc., and chalcogenide FeX representing 11 (X = chalcogenide) [4][5][6]. Eleven is the simplest family of FBS and has the highest T c of around 15 K for FeSe 1-x Te x (x = 0.5) samples at ambient pressure [3,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Due to these stable phases, it's always challenging to prepare a completely pure superconducting phase either in single crystal [14,15] or polycrystalline samples [3,7,16,17]. Some of these stable phases, particularly hexagonal δ-Fe x Se and hexagonal Fe 7 Se 8 , typically coexist with the predominant tetragonal β-Fe x Se phase [18] during the growth process and are not suitable for superconducting properties [19][20][21][22][23]. Recent research has demonstrated that convenient synthesis methods at ambient pressure (CSP) are inefficient for improving the critical current properties, grain connectivity, and phase purity of the bulk samples, as well as for practical applications [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%